The significance of clothing in minor forms of sexual harassment a survey among selected University of the Philippines students - Padre, Anne Beatrice T.
ABSTRACT Minor forms of sexual harassment such as catcalling and inappropriate touching have become a very common occurrence in the lives of Filipino women today. One of the excuses of the doer is the victim's provocative clothing. To validate the contribution of clothing to sexual harassment, a survey was conducted among male and female college students from a general education class in UP Diliman. A questionnaire was developed to determine the factors that motivate male university students to commit minor forms of sexual harassment, and if the victim's clothing is a significant factor, and to describe the type of clothing that provokes male students to commit minor forms of sexual harassment. Based on students' responses, clothing was perceived to be a significant factor motivating male students to commit minor forms of sexual harassment although it was considered less important as compared to facial attractiveness, body shape, and demeanor. On the other hand, female respondents perceived that environment has a significant contribution to occurrences of sexual harassment but not clothing. Both male and female respondents perceived that tight fitting, strapless, sleeveless, short skirts, and short shorts were most likely to encourage sexual harassment, however, in reality,, as shown in the results, those wearing what is considered a "normal style", like jeans and shirts are what gets targeted more often. Results from this study suggested that risk sexual harassment can be reduced through wearing a certain type of clothing. In addition, given the results, education among male Filipino university students may be encouraged to help change the outlook of how women are objectified sexually through what they wear.